Sustainable collaboration: a method to integrate discipline-sensitive information literacy modules at program levels - Süld, Karin; Bytoft-Nyaas, Eli (Nordic Journal of Information Literacy in Higher Education, 2010)
The Borås Model, a model on how the library and the university departments can collaborate to facilitate development of information literacy (IL) among students, is the outcome of a project run by the Library and Learning Resources and the School of Library and Information Science at the University of Borås. The model is a top-down-model and the Rector of the University of Borås in early 2009 made a decision that it should be implemented in all programs at the university. Thereby the senior administrators were given the responsibility to promote and facilitate sustainable collaboration between the university departments and the library to develop embedded IL modules through the curriculum. The overall analysis and planning to identify where IL modules should be integrated in a program is a responsibility shared by the director of studies and the teaching librarian. Course coordinators, teachers and the teaching librarian collaborate on writing learning outcomes for the actual IL module, decide the content, assignments and the overall design of the IL module. The implementation of the model is still in it’s cradle. There will surely be obstacles to overcome along the road as the model unfolds and it will surely take some time for everything to fall into place. But the goal is clear: to design embedded discipline sensitive IL modules to support the students’ development of information literacy, both for their needs as students but equally important to prepare them for their professional career. As a starting point for the implementation of the model the teaching librarians discussed what should be classified as basic knowledge and what should be classified as advanced knowledge in terms of information literacy. The discussions resulted in guidelines for the creation of IL modules with an emphasis of progression throughout the whole programs, but the guidelines are general enough to allow for adaptation to the specific needs of individual programs and the students’ various future professions. What was achieved during this first year reveals that the IL modules must indeed be allowed to differ in number and size as well as in content for the different programs. The presentation will give a few examples that will illustrate how learning outcomes can vary between different programs, and how the university’s learning management systems (LMS) is used for assignments and assessment. Finally it will present some lessons learned.